The Role of School Mads in Improving Visual Literacy in Utaseko School Students - Bili, Anjelina Rina; Ngura, Elisabeth Tantiana; Fono, Yasinta Maria; Meka, Marsianus (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research aims to investigate the role of school media in increasing visual literacy among SDI Utaseko students. School media is a simple and interactive mass communication medium. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews, and documentation, the research subjects were all SDI Utaseko students.Â  The research results show that school media can increase visual literacy in several ways: 1) increasing creativity: Mading allows students to create their content, such as pictures, illustrations, or infographics which increases creativity and interest in reading, 2) building a culture of literacy: media becomes a facility for students to express ideas and creativity in written form, thereby fostering a culture of literacy in schools, 3) improving Reading-Writing skills. Mading is used as a medium to improve students' reading and writing skills, as well as building students' reading habits, 4) developing critical reading skills: Mading allows students to think critically about the ideas and information presented, thereby improving critical thinking skills. This research shows that school media have an important role in increasing visual literacy among SDI Utaseko students. Thus, all media is used as an effective strategy for improving students' visual literacy skills.